The impacts of digital transformation on data-based ethical decision-making and environmental performance in Vietnamese manufacturing firms: The moderating role of organizational mindfulness - Nguyen Phong Nguyen; Tu Thanh Hoai (Cogent Business & Management, 2022)
Using the contingency theory of decision-making and a natural-resources-based view (NRBV) of the firm, we developed and tested a moderated mediation model examining (1) the impact of digital transformation on environmental performance (EP) via the mediating mechanism of data-based ethical decision-making (DEDM) and (2) the moderating role of organizational mindfulness in the effect of digital transformation on DEDM. The results of an analysis of 466 Vietnamese manufacturing firms indicate that DEDM mediates the impact of digital transformation on environmental performance. Moreover, the positive relationship between digital transformation and DEDM grows stronger as an organization's mindfulness level increases. The findings contribute to a more nuanced understanding of how digital transformation and organizational mindfulness play a vital role in environmental management practices.
Keywords: 650; Vietnam; Data-based ethical decision-making; digital transformation; environmental performance; organizational mindfulness